2021
DOI: 10.3389/fimmu.2021.786617
|View full text |Cite
|
Sign up to set email alerts
|

Influenza Neuraminidase Characteristics and Potential as a Vaccine Target

Abstract: Neuraminidase of influenza A and B viruses plays a critical role in the virus life cycle and is an important target of the host immune system. Here, we highlight the current understanding of influenza neuraminidase structure, function, antigenicity, immunogenicity, and immune protective potential. Neuraminidase inhibiting antibodies have been recognized as correlates of protection against disease caused by natural or experimental influenza A virus infection in humans. In the past years, we have witnessed an in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
26
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 194 publications
(265 reference statements)
1
26
0
1
Order By: Relevance
“…Influenza is a single-stranded, negative-sense RNA virus that contains two membrane-embedded glycoproteins: hemagglutinin (HA) and neuraminidase (NA). The viral envelope is also dotted with transmembrane proton channels named M2. , HA and NA are involved in a complex interplay whose combined functions include viral entry, progeny release, and evading host immune pressure. These processes are, in part, modulated by glycans, whose number and position can vary from year to year owing to the relentless evolution of the influenza virus. As a part of influenza seasonal antigenic drift, the introduced missense mutations may directly alter the antigenicity of HA and NA epitopes or sometimes result in the gain or loss of a glycosylation site, thus leading to shielding or unmasking of nearby epitopes. Antigenic drift means that vaccines targeting influenza need to be regularly updated to match the currently predominant strains of the virus. , Despite HA being the immunodominant protein, , NA also represents a potential vaccine target; knowledge of accessible and currently utilized epitopes is crucial in retaining influenza vaccine efficacy and in designing new vaccines. This is particularly relevant as the scientific community marches toward a universal influenza vaccine that is not affected by antigenic drift. ,, …”
Section: Introductionmentioning
confidence: 99%
“…Influenza is a single-stranded, negative-sense RNA virus that contains two membrane-embedded glycoproteins: hemagglutinin (HA) and neuraminidase (NA). The viral envelope is also dotted with transmembrane proton channels named M2. , HA and NA are involved in a complex interplay whose combined functions include viral entry, progeny release, and evading host immune pressure. These processes are, in part, modulated by glycans, whose number and position can vary from year to year owing to the relentless evolution of the influenza virus. As a part of influenza seasonal antigenic drift, the introduced missense mutations may directly alter the antigenicity of HA and NA epitopes or sometimes result in the gain or loss of a glycosylation site, thus leading to shielding or unmasking of nearby epitopes. Antigenic drift means that vaccines targeting influenza need to be regularly updated to match the currently predominant strains of the virus. , Despite HA being the immunodominant protein, , NA also represents a potential vaccine target; knowledge of accessible and currently utilized epitopes is crucial in retaining influenza vaccine efficacy and in designing new vaccines. This is particularly relevant as the scientific community marches toward a universal influenza vaccine that is not affected by antigenic drift. ,, …”
Section: Introductionmentioning
confidence: 99%
“…Immunoglobulin is the most abundant domain found among the 2419 unique mouse proteins containing interacting SCOP domains (Supplementary Figure S4) . During natural infection with IAVs, immune response against both HA and NA will be evoked [8]. IgM response is dominant in primary infection, while IgG response is dominant in secondary infection, for Ig secretion.…”
Section: Discussionmentioning
confidence: 99%
“…Currently licensed influenza vaccines are majorly formulated and optimized based on the HA antigen [ 4 ], whereas NA is not utilized in these vaccines. However, several studies have revealed the importance of NA as a vaccine antigen [ 5 , 6 ]. Importantly, anti-NA antibodies elicited a protective effect against the influenza virus [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, cross-protective anti-NA antibodies were generated after a seasonal vaccination with a single influenza viral strain, A/California/07/2009 (subtype A (H1N1) pdm09) [ 11 ]. Due to these beneficial characteristics, NA has been suggested as a good antigen candidate to improve the breadth of vaccine efficacy and is applicable to vaccine design [ 6 ].…”
Section: Introductionmentioning
confidence: 99%